Zn-Co metal organic frameworks coated with chitosand and Au nanoparticles for chemo-photothermal-targeted combination therapy of liver cancer - Yang, Congling; Tiwari, Santosh K.; Guo, Lianshan; An, Guanghui; Zheng, Heming; Huang, JianFeng; Jiang, Li; Bai, Zhihao; Zhu, Yanqiu; Wang, Nannan (Frontiers in Oncology, 2023)
The toxic effects of chemotherapeutic drugs on normal tissues are still a major limiting factor in cancer treatment. In this paper, a metal-organic framework (Zn-Co ZIF) loaded with liver cancer therapeutic drug adriamycin hydrochloride (DOX), and coated with an outer layer of chitosan was reported as new enhanced nano-drug delivery for cancer therapy. Gold nanoparticles as good photothermal converters are introduced to the exterior of Zn-Co ZIF@DOX-CS and externally connected to Mercapturized RGD (SH-RGD) for the targeted therapy of liver cancer. Then, Zn-Co ZIF@DOX-CS-Au-RGD (ZD-CAR) was prepared. After the RGD targeted the tumour and entered the tumour microenvironment, the liver cancer treatment drug (DOX) was released to kill the tumour cells efficiently. The metal skeleton cleaved and released Co2+, which could catalyze the production of oxygen from H2O2 to alleviate the tumour hypoxic environment. Dissolved oxygen could reach up to 14 mg/L after 80 μg/ml of ZD-CAR was added. In the meantime, the gold nanoparticles can convert light energy into heat energy under 808 NIR irradiation to induce local superheating and kill tumor cells. ZD-CAR doped with 50% cobalt, showed optimum size and performance, and could cleave and release the drug in a weakly acidic tumour microenvironment (TME). In summary, this study has developed a nanoplatform that combines chemo-photothermal-targeted therapy. It has shown good therapeutic efficiency in cellular experiments and performance tests and has promising applications in anti-cancer treatment.